2022
DOI: 10.1002/aic.17876
|View full text |Cite
|
Sign up to set email alerts
|

Development and verification of coarse‐grain CFD‐DEM for nonspherical particles in a gas–solid fluidized bed

Abstract: Computational fluid dynamics coupled with discrete element method (CFD‐DEM) has been widely used to understand the complicated fundamentals inside gas–solid fluidized beds. To realize large‐scale simulations, CFD‐DEM integrated with coarse‐grain model (CG CFD‐DEM) provides a feasible solution, and has led to a recent upsurge of interest. However, when dealing with large‐scale simulations involving irregular‐shaped particles such as biomass particles featuring elongated shapes, current CG models cannot function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…There has been a great deal of reliance on Eulerian-Eulerian methods in the past, specifically the two-fluid model in fluidized-bed studies [11][12][13]. The CFD-discrete element method (CFD-DEM) exhibits more advantages for predicting binary solid mixing in a fluidized bed than the Eulerian-Lagrangian methods and can provide critical information at the level of individual particles, such as particle trajectory, forces acting on individual particles, and the property changes of particles [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great deal of reliance on Eulerian-Eulerian methods in the past, specifically the two-fluid model in fluidized-bed studies [11][12][13]. The CFD-discrete element method (CFD-DEM) exhibits more advantages for predicting binary solid mixing in a fluidized bed than the Eulerian-Lagrangian methods and can provide critical information at the level of individual particles, such as particle trajectory, forces acting on individual particles, and the property changes of particles [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A popular method for simulating gas-solid multiphase flow is the CFD coupled with discrete element method (CFD-DEM) approach, which is a highfidelity modeling regime to resolve solid motion and collision. 18 Via this approach, numerous reports have been carried out to investigate biomass fast pyrolysis. [19][20][21] However, the CFD-DEM fails to simulate multiphase flow in large-scale apparatus because of prohibitive computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…To make up for this deficiency, the Eulerian–Lagrangian framework has been introduced where the fluid phase is still solved as continuum by the Navier–Stokes (N–S) equations while the solid phase is regarded as discrete elements and tracked by the Newton's Law. A popular method for simulating gas–solid multiphase flow is the CFD coupled with discrete element method (CFD‐DEM) approach, which is a high‐fidelity modeling regime to resolve solid motion and collision 18 . Via this approach, numerous reports have been carried out to investigate biomass fast pyrolysis 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most extensively researched methods is presented in ref . Subsequently, fluidized beds were studied using this scaling law. Several other coarse-graining techniques exist; see, for example, refs . However, based on the review in ref , it is clear that research is mainly focused on bed hydrodynamics, and only a few literature studies reported coarse-graining scaling laws for gas-particle heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%